The Effect of Papaya Leaf Extract (Carica papaya L.) on Erythrocyte Values in Anemia-Model Rats - Fajar Dwi Susanto; Leny Yulia Widia Sari; Ahdiah Imroatul Muflihah; Anas Fadli Wijaya; Ayu Tri Agustin (LPPM Universitas dr. Soebandi, 2025)
Background: Anemia remains a significant public health challenge with a global prevalence of 40-88%. Papaya leaf extract (Carica papaya L.) contains bioactive compounds such as flavonoids, vitamin C, and vitamin E that potentially enhance erythrocyte production. Purpose: This study aimed to determine the effect of papaya leaf extract on erythrocyte values in anemia-model rats (Rattus novergicus). Methods: An experimental laboratory study was conducted from April to June 2025 using 25 rats divided into 5 groups: positive control (sodium nitrite), negative control (aquadest), and three treatment groups receiving papaya leaf extract at doses of 100, 200, and 400 mg/kg BW. Anemia was induced using sodium nitrite at 50 mg/kg BW via intraperitoneal injection. Erythrocyte measurements were performed using a hematology analyzer. Data were analyzed using Shapiro-Wilk normality test, Levene's homogeneity test, one-way ANOVA followed by Tukey HSD (α=0.05). Results: Treatment group P3 (dose 400 mg/kg BW) demonstrated the highest erythrocyte value of 12.066±0.84 (10⁶/µL), followed by P1 (11.576±0.71), P2 (11.496±1.19), negative control (10.728±1.01), and positive control (6.220±1.96). ANOVA test revealed significant differences between groups (p<0.001). Conclusions: Papaya leaf extract increases erythrocyte values in anemia-model rats, with 400 mg/kg BW being the most effective dose.